Strength of Modified Foam Concrete Filled Hollow Section Using fly ash as Sand Replacement Added Polypropylene Fibre - Ramli, Nurul Syahirah; Abd Rahman, Norashidah (Recent Trends in Civil Engineering and Built Environment, 2022)
Concrete-filled hollow section (CFHS) was widely used in steel construction such as bridge, building and other structures in these previous years and the combination of concrete and steel will prevent buckling and deforming happened to the concrete-filled hollow section (CFHS). The aim of this study is to determine the strength of lightweight concrete filled hollow section filled hollow section added polypropylene fibre and to compare the strength of lightweight cellular concrete filled hollow section added with polypropylene fibre with foamed concrete filled hollow section. In this experimental study, a square type of hollow section was used with a volume of 100mmx100mmx350mm with two different thicknesses used in the experiment namely 2mm and 4mm. The compression test and cube test are the main lab tests for this project to determine the strength of the lightweight cellular concrete filled hollow section added polypropylene fibre. The additional polypropylene fibre with fly ash improves concrete strength and is utilised in the steel industrial sector as filled concrete.